PEMINATAN SISWA TERHADAP PEMBELAJARAN EKONOMI KELAS X SMA NEGERI 13 MERANGIN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students’ interest in learning economics in grade X at SMA Negeri 13 Merangin. Student interest plays an important role in determining learning success, particularly in subjects that require conceptual understanding such as economics. This research employed a quantitative descriptive approach. The population consisted of all grade X students of SMA Negeri 13 Merangin, with samples selected using proportional random sampling. Data were collected through questionnaires and analyzed using descriptive statistical techniques. The results indicate that students’ interest in learning economics is categorized as moderate. Factors influencing student interest include teaching methods, learning media, teacher student interaction, and the relevance of learning materials to daily life. These findings suggest the need for innovative teaching strategies to improve students’ interest in learning economics.